Guidebook for deploying distributed renewable energy systems a case study on the Cobrador Hybrid Solar PV Mini-Grid. (Asia bond monitor., 2019)
Affordable, reliable, sustainable, and modern energy for all that meets environmental goals is central to global development and policy making. Access to electricity continues to improve in Asia and the Pacific, yet many rural areas lag behind due to challenges in the economic and financial viability of grid extensions. This publication discusses the advantages of distributed renewable energy systems as a solution. It also outlines techniques and tools to optimize renewable energy resources for off-grid electrification that can complement and supplement national energy plans and programs.